Pollinating fig wasp and seed productions of Ficus deltoidea var. angustifolia at selected oil palm plantations in Peninsular Malaysia - Noor Nasuha A. A.,; Siti Khairiyah M. H.,; Idris Abd. Ghani, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2017)
The relationship between Ficus deltoidea (family Moraceae) and pollinator fig wasp (family Agaonidae) are extremely specific in which each partner depends on the other for their reproductive success. There are about seven described varieties of Ficus deltoidea can be found in peninsular Malaysia. Ficus deltoidea is a dioecious species that are primarily epiphytes. They are unharmful for their host tree where one of the host tree is oil palm tree. In this study, epiphytic Ficus deltoidea var. angustifolia from oil palm plantations in Banting, Dengkil, Changkat Lobak and Batu Pahat, Malayaia were studied to determine the flower variation and reproductive output (fig wasp and seeds) by the figs of different individual plants and locations. A total of ten matured figs from each male and female tree from all locations were collected and later dissected to count the number of flowers, galls, female and male fig wasp for male tree while the number of seed and female flowers were counted from female tree. Data were analysed by using one-way ANOVA. Overall results showed that different individual plants were significantly varied in their floral numbers and reproductive output (pollinators and seeds) (P < 0.05) for both and male figs except for seed productions at Changkat Lobak (P = 0.067). Whilst there were significant different (P < 0.01) in the production of pollinators and seeds by the figs among locations. The reproductive output (pollinators and seeds) were greatly influenced by number of flowers and number of fig wasp visitations per fig.